Rates of hospitalization associated with the use of aldosterone receptor antagonists in patients with pulmonary arterial hypertension. (1st August 2019) - Corkish, Morgan E.; Devine, Lauren T.; Clarke, Megan M.; Murray, Brian P.; Rose‐Jones, Lisa J.
Abstract : We show that spironolactone use was associated with an increased rate of all‐cause hospitalizations, but no difference in hospitalizations for heart failure or pulmonary arterial hypertension, in patients with World Health Organization Group 1 pulmonary arterial hypertension. A possible reason for this finding is confounding from retrospective study design.